Предмет: Математика,
автор: ladcakey
Пжжжжж помогите быстрее даб 50 баллав Нати решение и Упростить (х+3)*(3х-1) - ( х+2)*(х-5) при х = - 2
Ответы
Автор ответа:
0
Ответ:
37
Пошаговое объяснение:
3х² - х + 9х - 3 - х² + 5х - 2х + 10 = 2х² + 11х + 7, при х=-2 получаем:
8 + 22 + 7 = 37
Похожие вопросы
Предмет: Информатика,
автор: DemberBit
Предмет: Информатика,
автор: dimaaa9090508
Предмет: Математика,
автор: thisismyniknameHELP2
Предмет: Математика,
автор: соня578
Предмет: Математика,
автор: соня578